Ionizing pressure sensor capable of realizing high sensitivity and low drift through body capacitance strategy and preparation method and application of ionizing pressure sensor
By using the ionized composite materials and body capacitance strategies based on the epoxy group, the existing ionized pressure sensor's contradiction between high sensitivity and low drift is solved, and high -sensitive and low drift pressure sensors are achieved. A variety of application scenarios.
Patent Information
- Application Number
- CN202411483765.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing unchangeable flexible pressure sensors have a contradiction between high sensitivity and low drift, making it difficult to achieve high sensitivity and low drift at the same time.
Using an ionizing composite material based on epoxy groups, material A (epoxy-based ionic liquid), material B (organic polyamine compound or polyetheramine) and material C (conductive filler, such as carbon nanotubes) are mixed in a solvent The composite material is uniformly dispersed and cured as the sensor material layer, and combined with the bulk capacitance strategy to achieve a highly sensitive, low-drift ionization pressure sensor.
The pressure sensor of high sensitivity and low signal drift can be achieved, which can provide accurate pressure feedback in complex environments, and it is suitable for human -computer interaction and wearable medical equipment.
Smart Images

Figure CN119331223A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sensors, and in particular relates to an ion-type pressure sensor that achieves high sensitivity and low drift through a body capacitance strategy, and a preparation method and application thereof. Background Art
[0002] In recent years, with the portability of health monitoring equipment and the diversification of sensor equipment applications, flexible pressure sensors have been widely used as an important type of information collection device. It has properties similar to human skin. By covering the surface of any carrier to measure force information, it can sense the properties of the target object and convert the received information into electrical signals or other signal outputs according to certain rules, providing a strong guarantee for the development of the Internet of Things. Compared with traditional rigid sensors, flexible pressure sensors have greater advantages when used on complex curved surfaces due to their good ductility and flexibility. The breakthrough from rigidity to flexibility has greatly expanded the application scenarios of sensors.
[0003] Flexible capacitive pressure sensors have attracted extensive attention in the field of high-performance sensing technology due to their high drift stability and simple structure. However, these sensors show low sensitivity under wide pressure ranges or high pressure conditions and are prone to saturation, which severely limits their application potential in extreme environments. In order to solve the problems of low sensor sensitivity and low signal-to-noise ratio, a new type of "ion-electric" flexible pressure sensor has emerged in recent years. By forming a double electric layer when the electrode and the ion conductor are in contact, a larger unit area capacitance is generated at the interface, making the sensitivity of the ion-electric pressure sensor several orders of magnitude higher than that of the traditional capacitive pressure sensor. In addition, due to its low preparation cost, simple process, and flexible deformation, it is also widely used in emerging fields such as health monitoring, wearable electronic devices, human-computer interaction, virtual reality, and soft robots.
[0004] The existing ion-type flexible pressure sensors are mainly divided into the following two categories: the first is an ion gel-based flexible pressure sensor; the other is a polyion elastomer-based flexible pressure sensor. Both have shown excellent sensing performance in different application scenarios, but both have obvious shortcomings.
[0005] For ion gel-based flexible pressure sensors: ion gel is a material composed of polymer network and electrolyte ions, and its conductivity changes with the change of ion concentration and distribution. When pressure is applied, the structure and ion distribution of ion gel will change, thus affecting its capacitance, and the sensor determines the applied pressure by measuring these electrical changes. Ion gel-based ion-type pressure sensors often have better device sensitivity and signal-to-noise ratio, especially when the sensor detects small pressures, the signal change is more obvious. Not only that, because there is no chemical bond connection between the ion material and the polymer network, the migration speed of ions in the polymer matrix also makes it have high sensitivity. However, ion gels usually contain a large amount of liquid electrolyte. Its structure is relatively loose, and the electrolyte ions exist in liquid state. Long-term load will increase ion migration and material fluidity, resulting in significant material creep. Creep of ion gel materials will cause changes in the geometry of the sensing material, such as thickness change, dimensional deformation, etc. This geometric change will directly affect the capacitance measurement principle of the sensor, resulting in signal drift, making it impossible to achieve accurate feedback on pressure, greatly reducing its practical application value. In addition, ion gel materials may leak ionic liquids under high pressure conditions, which will not only cause sensor failure or affect the surrounding environment, but also cause certain biocompatibility problems.
[0006] For polyion elastomer-based flexible pressure sensors: polyion elastomers are a type of polymer material that fixes one or both of anions and cations on the molecular chain. Since some or all of the ions are fixed on the molecular chain, the conductivity of such materials is usually low under low temperature conditions, which may also limit the free mobility of ions, slow electrical response, and greatly reduce the sensitivity of the device. However, polyion elastomers usually have less creep than ion gels, because polyion elastomers are composed of elastic polymer networks and ion conductive components. Its structure usually includes a highly cross-linked polymer network, which provides good mechanical strength and elasticity, so that the material deforms less when subjected to long-term loads. In addition, the ions are fixed on the molecular chain, which restricts the migration of ions, which reduces the free mobility inside the material, thereby reducing the creep of the functional material, which also provides the possibility for the ion-type flexible pressure sensor to have the characteristic of drift-free. This network structure firmly locks the ions on the polymer chain to form a stable solid structure with limited ion mobility. This solid structure is less likely to migrate or leak under external force than ion gels containing a large amount of liquid electrolyte. Therefore, it can accurately feedback pressure information and is widely used in technical fields that require precise measurement, such as human-computer interaction and wearable medical devices.
[0007] Both types of ion-type flexible pressure sensors have certain advantages and disadvantages. Ion gel-based ion-type pressure sensors have the characteristics of high sensitivity and high signal-to-noise ratio, but are prone to problems such as sensor signal drift and ion leakage, resulting in inaccurate sensor signals and cannot be used for long-term static pressure measurements. Polyion elastomer-based ion-type pressure sensors have the characteristics of no leakage and low creep, which makes the ion-type pressure sensor have the characteristics of no signal drift and can be used for long-term stable and accurate feedback of pressure information, but sensors based on this type are often not very sensitive, with low sensitivity and resolution, resulting in low detection accuracy, and are not suitable for applications that require high precision and high sensitivity, such as biomedical sensing, precision manufacturing and scientific research.
[0008] Therefore, how to simultaneously achieve high sensitivity and low drift of the ionization pressure sensor has become a top priority in research in this field, and is also a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0009] The object of the present invention is to provide a method for preparing an ionizing composite material based on epoxy groups, comprising the following steps: uniformly dispersing material A, material B and material C in a solvent; evaporating the solvent from the obtained dispersion, and then curing to obtain an ionizing composite material based on epoxy groups; wherein material A is an ionic liquid having epoxy groups, including epoxy ionic liquid 1 and / or epoxy ionic liquid 2; material B includes an organic polyamine compound or a polyether amine; and material C is a conductive filler.
[0010] In a preferred embodiment, the material B includes tris(2-aminoethyl)amine and / or 2,2'-(ethylenedioxy)bis(ethylamine), and the material C includes carbon nanotubes and / or carboxyl-modified carbon nanotubes.
[0011] In a preferred embodiment, the molar ratio of material A to material B is 2:(0.5-2), and the material C is 2%-5% of the mass of material A; preferably, the molar ratio of material A to material B is 2:1, and the material C is 3%-4% of the mass of material A.
[0012] In a preferred embodiment, the solvent is an organic solvent; preferably, the organic solvent includes acetone; more preferably, the amount ratio of the material A to the solvent is 3mmol:(10-200)g; most preferably, the amount ratio of the material A to the solvent is 3mmol:(20-100)g.
[0013] In a preferred embodiment, in order to improve the dispersion effect of material A, material B and material C in the solvent, ultrasonic dispersion can be used for 1-2 hours.
[0014] In a preferred embodiment, the curing includes light curing or heat curing; preferably, the heat curing temperature is 70-80° C., and the heat curing time is 1-2 hours.
[0015] In a preferred embodiment, the epoxy ionic liquid 1 is prepared by the following method:
[0016] S1: Dissolve imidazole, sodium bicarbonate and 4-bromo-1-butene in acetonitrile, heat to reflux, and after the reaction is completed, filter and evaporate to obtain a crude product; purify the crude product with dichloromethane and an extractant; add a concentrated LiTFSI solution dropwise to the purified product until no oily precipitate is produced, suck out the upper aqueous phase, extract impurities with deionized water, and remove residual moisture; the reaction path of step S1 in preparing epoxy ionic liquid 1 is shown in Formula I.
[0017]
[0018] S2: dissolving the reaction product of step S1 and m-chloroperbenzoic acid in acetonitrile, reacting at room temperature for a period of time, filtering, and rotary evaporating to obtain a crude product; purifying the crude product with ether to obtain epoxy ionic liquid 1; the reaction path of step S2 in preparing epoxy ionic liquid 1 is shown in formula II.
[0019]
[0020] Further preferably, in step S1, the molar ratio of imidazole, sodium bicarbonate and 4-bromo-1-butene is 1:(0.8-1.2):(1.7-2.55); preferably, the molar ratio of imidazole, sodium bicarbonate and 4-bromo-1-butene is 1:1:2.13.
[0021] Further preferably, in step S1, the molar volume ratio of imidazole to acetonitrile is 1 mmol:(0.5-0.75) ml; preferably, the molar volume ratio of imidazole to acetonitrile is 1 mmol:0.625 ml.
[0022] Further preferably, in step S1, the heating reflux temperature is 70-80°C, and the heating reflux time is 12-36h; preferably, the heating reflux temperature is 75°C, and the heating reflux time is 24h.
[0023] Further preferably, in step S1, the purification of the crude product comprises the following steps: dissolving the crude product with dichloromethane, drying, filtering, and rotary evaporating to remove dichloromethane; then dissolving with deionized water, respectively extracting with ethyl acetate, n-hexane and ether to remove impurities. Preferably, the purpose of the drying method is to remove moisture, and conventional methods known to those skilled in the art can be used, such as adding anhydrous magnesium sulfate. More preferably, the method for extracting impurities can be used conventional methods known to those skilled in the art. Most preferably, the number of extractions with ethyl acetate is 1-3 times, the number of extractions with n-hexane is 1-2 times, and the number of extractions with ether is 1-2 times.
[0024] Further preferably, in step S1, the LiTFSI concentrated solution includes a saturated solution of LiTFSI or a solution with a mass fraction of 50%.
[0025] Further preferably, in step S1, the extraction times with deionized water is 1-5 times, and the method for removing residual water can adopt conventional methods known to those skilled in the art, such as vacuum freeze-drying for 6-12 hours.
[0026] Further preferably, in step S2, the molar ratio of the reaction product of step S1 to meta-chloroperbenzoic acid is 1:(3.2-4.8); preferably, the molar ratio of the reaction product of step S1 to meta-chloroperbenzoic acid is 1:4.
[0027] Further preferably, in step S2, the ratio of the reaction product of step S1 to acetonitrile is 1 mmol:(1.25-1.88) g; the ratio of the reaction product of step S1 to acetonitrile is 1 mmol:1.56 g.
[0028] Further preferably, in step S2, the room temperature reaction time is 24-48 hours; preferably, the room temperature reaction time is 36 hours.
[0029] Further preferably, in step S2, the purification of the crude product comprises the following steps: dissolving the crude product with ether, extracting impurities with ether after oily precipitation, and then vacuuming the purified product to remove residual ether. Preferably, the ethyl acetate extraction is performed 1-4 times.
[0030] In a preferred embodiment, the epoxy ionic liquid 2 is prepared by the following method:
[0031] Dissolve imidazole, sodium carbonate, epichlorohydrin and LiTFSI concentrated solution in acetonitrile, heat and reflux, and after the reaction is completed, filter and evaporation are performed to obtain a crude product; the crude product is purified with deionized water to obtain epoxy ionic liquid 2. The reaction path for preparing epoxy ionic liquid 2 is shown in Formula III.
[0032]
[0033] Further preferably, the dosage ratio of the imidazole, sodium carbonate, epichlorohydrin and LiTFSI concentrated solution is 1 mmol: (1.6-2.4) mmol: (1.6-2.4) mmol: (0.23-0.34) g; preferably, the dosage ratio of the imidazole, sodium carbonate, epichlorohydrin and LiTFSI is 1 mmol: 2 mmol: 2 mmol: 0.29 g.
[0034] Further preferably, the LiTFSI concentrated solution includes a saturated solution of LiTFSI or a solution with a mass fraction of 50%.
[0035] Further preferably, the usage ratio of imidazole to acetonitrile is 1 mmol:(0.8-1.2) g; preferably, the usage ratio of imidazole to acetonitrile is 1 mmol:1 g.
[0036] Further preferably, the heating reflux temperature is 70-80°C, and the heating reflux time is 12-36h; preferably, the heating reflux temperature is 75°C, and the heating reflux time is 24h.
[0037] Further preferably, the crude product purification comprises: extracting impurities with deionized water and then removing residual water by vacuum freeze drying. Preferably, the deionized water extraction times are 1-10 times, and the vacuum freeze drying time is 6-12 hours.
[0038] Another object of the present invention is to provide an ionizing composite material based on epoxy groups prepared by any of the above methods.
[0039] Another object of the present invention is to provide a highly sensitive, low drift ionization pressure sensor, comprising a sensor material layer, an electrode layer and a packaging layer, wherein the sensor material layer comprises an ionization composite material based on epoxy groups prepared by any of the above methods, the packaging layer comprises a PDMS film, and the electrode layer comprises a PI / Cu composite film.
[0040] Another object of the present invention is to provide a method for preparing a high-sensitivity, low-drift ionization pressure sensor, which specifically includes aligning and packaging an upper packaging layer, an upper electrode layer, a sensing material layer, a lower electrode layer and a lower packaging layer from top to bottom.
[0041] Another object of the present invention is to provide a high-sensitivity, low-drift ionization pressure sensor for use in the fields of human-computer interaction and wearable medical devices.
[0042] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0043] The present invention provides an ionizing composite material based on epoxy groups and a preparation method thereof, which is then used as a sensor material layer to realize a general method of a high-sensitivity, low-drift ionizing pressure sensor through a body capacitance strategy. In the present invention, firstly, a polyion elastomer is selected as the functional material body to effectively reduce creep and greatly reduce signal drift. Secondly, the conductivity and sensitivity of the sensor are improved by adding conductive fillers to the polyion elastomer. A synergistic effect occurs between the conductive filler and the ions in the polyion elastomer, greatly improving the conductivity. Not only that, the ions conducted in the polymer and the electrons conducted in the filler form many tiny capacitors. These capacitors can be connected in series or in parallel, which will further improve the sensitivity of the capacitive sensor. The specific principle is as follows Figure 1 As shown. Finally, by using the prepared composite material of polyionic elastomer and conductive filler as the sensing functional material layer, a highly sensitive, low-drift ion-type pressure sensor can be assembled. The obtained sensor has broad application prospects in technical fields such as human-computer interaction and wearable medical devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:
[0045] Figure 1 This is a schematic diagram of the body capacitance sensing principle provided by the present invention;
[0046] Figure 2 is the electrical conductivity of the ionizing composite material of Example 3 of the present invention;
[0047] Figure 3 is the electrical conductivity of the ionizing composite material of Example 4 of the present invention;
[0048] Figure 4 is the electrical conductivity of the ionizing composite material of Example 5 of the present invention;
[0049] Figure 5 The conductivity of the polyion elastomer without conductive filler in Comparative Example 1 of the present invention;
[0050] Figure 6 This is the sensitivity curve of the ionizing composite material of Example 3 of the present invention;
[0051] Figure 7 This is the sensitivity curve of the ionizing composite material of Example 4 of the present invention;
[0052] Figure 8 This is the sensitivity curve of the ionizing composite material of Example 5 of the present invention;
[0053] Fig. 9 This is the sensitivity curve of the ionizing composite material of Comparative Example 1 of the present invention;
[0054] Fig.10 It is the sensitivity comparison curve of the experimental group and the control group of the present invention;
[0055] Fig.11 This is the signal drift curve of the ionized composite material of Example 3 of the present invention;
[0056] Fig.12 This is the signal drift curve of the ionized composite material of Example 4 of the present invention;
[0057] Fig.13 This is the signal drift curve of the ionized composite material of Example 5 of the present invention;
[0058] Fig.14 This is the signal drift curve of the ionizing composite material of comparative example 1 of the present invention. DETAILED DESCRIPTION
[0059] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but it should be understood that the protection scope of the present invention is not limited to the specific implementation methods.
[0060] Unless otherwise specified, the technical means used in the present invention are conventional means well known to those skilled in the art, and the various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The reagents used in the present invention are analytically pure unless otherwise specified.
[0061] Example 1
[0062] Synthesis of epoxy ionic liquid 1:
[0063] Preparation: Imidazole (80 mmol, 5.5 g), sodium bicarbonate (80 mmol, 6.76 g), 4-bromo-1-butene (170 mmol, 23.65 g) were dissolved in 50 mL of acetonitrile, heated to 75°C, and refluxed for 24 h. After the reaction was completed, the mixture was cooled, filtered, and rotary evaporated to obtain a crude product.
[0064] Purification: Dissolve the crude product in dichloromethane, add anhydrous magnesium sulfate to dry, filter, and remove dichloromethane by rotary evaporation. Dissolve it in deionized water, extract impurities with ethyl acetate 3 times, hexane once, and ether once.
[0065] Ion replacement: LiTFSI concentrated solution was added dropwise until no oily precipitate was produced, the upper aqueous phase was aspirated, impurities were extracted with deionized water for 5 times, and then the residual water was removed by vacuum freeze drying for 12 hours.
[0066] Functionalization: The product of the previous step (8 mmol, 3.659 g) and m-chloroperbenzoic acid (32 mmol, 6.496 g) were dissolved in 12.5 g of acetonitrile and reacted at room temperature for 36 hours. The mixture was filtered and evaporated to obtain a crude product.
[0067] Purification: The crude product was dissolved in ether to produce an oily precipitate. The impurities were extracted with ether four times, and the remaining ether was removed by vacuum to complete the preparation of epoxy ionic liquid 1.
[0068] Example 2
[0069] Synthesis of epoxy ionic liquid 2:
[0070] Preparation: Imidazole (20 mmol, 1.36 g), sodium carbonate (40 mmol, 2.88 g), epichlorohydrin (40 mmol, 3.7 g), and LiTFSI (5.74 g) were dissolved in 20 g of acetonitrile, heated to 75°C, and refluxed for 24 h. After the reaction was completed, the mixture was cooled, filtered, and rotary evaporated to obtain a crude product.
[0071] Purification: The impurities were extracted with deionized water 10 times and then the residual water was removed by vacuum freeze drying for 12 hours to complete the preparation of epoxy ionic liquid 2.
[0072] Example 3
[0073] Synthesis of ionomeric composites containing conductive fillers:
[0074] 6mmol of epoxy ionic liquid 1, 3mmol of 2,2'-(ethylenedioxy)bis(ethylamine) and 0.1285g of carboxyl-modified carbon nanotubes (4% of the monomer mass) conductive filler prepared in Example 1 were ultrasonically dispersed in 50g of acetone solvent for 2h to obtain a dispersion. Subsequently, the dispersion was dropped onto a glass plate to volatilize the solvent, and after the solvent volatilized, it was placed on a hot plate at 80 degrees Celsius for curing. After curing for two hours, a composite ionized material of a polyionic elastomer and carboxyl carbon nanotubes was obtained. Its synthesis path is shown in Formula IV.
[0075]
[0076] Example 4
[0077] Synthesis of ionomeric composites containing conductive fillers:
[0078] 6mmol of epoxy ionic liquid 2, 3mmol of polyetheramine D-2000 and 0.3575g of carbon nanotube (3% of monomer mass) conductive filler modified by carboxyl group prepared in Example 2 were ultrasonically dispersed in 200g of acetone solvent for 2h to obtain a dispersion. Subsequently, the dispersion was dropped on a glass plate to volatilize the solvent, and after the solvent volatilized, it was placed on a hot stage at 80 degrees Celsius for curing. After curing for two hours, a composite ionized material of polyionic elastomer and carboxyl carbon nanotube was obtained. Its synthesis path is shown in Formula V.
[0079]
[0080] Example 5
[0081] Synthesis of ionomeric composites containing conductive fillers:
[0082] 6mmol of epoxy ionic liquid 2, 3mmol of tris(2-aminoethyl)amine and 0.1013g of carbon nanotube (3% of the monomer mass) conductive filler prepared in Example 2 were ultrasonically dispersed in 40g of acetone solvent for 2h to obtain a dispersion. Subsequently, the dispersion was dropped onto a glass plate to volatilize the solvent, and after the solvent evaporated, it was placed on a hot plate at 80 degrees Celsius for curing. After curing for two hours, a composite ionized material of polyionic elastomer and carbon nanotube was obtained. Its synthesis path is shown in Formula VI.
[0083]
[0084] Comparative Example 1
[0085] Synthesis of polyion elastomers without conductive fillers:
[0086] 4 mmol of the epoxy ionic liquid 1 prepared in Example 1 was mixed with 2 mmol of 2,2′-(ethylenedioxy)bis(ethylamine), shaken for 5 minutes, poured onto a glass plate, and cured at 80 degrees Celsius for two hours to obtain a polyionic elastomer, the synthesis route of which is shown in Formula VII.
[0087]
[0088] Effect Example 1
[0089] The ionized composite materials containing conductive fillers prepared in Examples 3-5 (experimental group) and the polyionic elastomer without conductive fillers prepared in Comparative Example 1 (control group) were tested using a broadband dielectric impedance spectrometer at 10 0 ~10 6 Changes in conductivity at Hz frequencies.
[0090] Results and discussion: The test results show that in 10 3The conductivity of Comparative Example 1 under the test condition of Hz alternating current is about 1.84×10 -7 S / cm, while the conductivity of the ionized composite materials of Examples 3-5 were 1.05×10 -4 S / cm, 1.70×10 -6 S / cm and 1.175×10 -4 S / cm. It can be seen that the conductivity of the material in the experimental group using the bulk capacitance strategy increased by 1-3 orders of magnitude compared to the control group, which further reflects the significant effect of the bulk capacitance effect on improving conductivity, providing the possibility for the preparation of highly sensitive sensors. The specific data is shown in the attached Figure 2-5 shown.
[0091] Effect Example 2
[0092] The ionized composite materials containing conductive fillers prepared in Examples 3-5 (experimental groups 1-3 respectively) and the polyion elastomer without conductive fillers prepared in Comparative Example 1 (control group 1) were used as sensing material layers of sensors to prepare sensors for sensitivity tests and signal drift tests.
[0093] The preparation method of the sensor specifically includes: aligning and encapsulating an upper encapsulation layer, an upper electrode layer, a sensing material layer, a lower electrode layer and a lower encapsulation layer in order from top to bottom, wherein the encapsulation layer is a PDMS film; the electrode layer is a PI / Cu composite film; and the sensing material layer is the material prepared in Examples 3-5 and Comparative Example 1.
[0094] Results and Discussion:
[0095] (I) Sensitivity is a physical quantity that characterizes the sensitivity of the pressure sensor to external pressure, which is the change in output caused by each kilopascal pressure range. High sensitivity is very important for flexible pressure sensors because it can detect extremely small pressure changes, ensuring that the sensor can still provide accurate and reliable measurements in complex and changing environments. For capacitive flexible pressure sensors, sensitivity is defined as the change in capacitance signal relative to the initial capacitance value under unit pressure, that is, S = δ(ΔC / C0) / δP, where S represents sensitivity (kPa –1 ), P represents pressure (kPa), C represents capacitance when loaded (pF), and C0 represents the initial capacitance value when no load is applied. We used a compression fatigue tester to test the sensitivity of the flexible pressure sensor prepared based on the polyion elastomer control group and the ion composite material experimental group, and recorded the change curve of the sensor's capacitance signal with pressure. After data processing, a curve with pressure as the horizontal axis and capacitance change rate as the vertical axis was obtained, and the slope of the curve is the sensitivity of the device.
[0096] The data results show that the pressure sensor prepared based on the polyionic elastomer control group (Comparative Example 1) has a lower device sensitivity, only 0.44 kPa –1 , while the sensors prepared by the ionization composite materials of Examples 3-5 have 15 kPa –1 , 6.5kPa –1 and 3382 kPa –1 The sensitivity of the prepared sensor is 1-3 orders of magnitude higher than that of the traditional polyion elastomer. The specific experimental results are shown in the attached Figure 6-10 shown.
[0097] (ii) Signal drift is a common phenomenon in flexible pressure sensors, especially under high-pressure working conditions. When the pressure on the sensor is close to the modulus, the signal drift phenomenon is more obvious. This makes it impossible for flexible pressure sensors to achieve accurate feedback of pressure, reducing their practical application value. Therefore, sensors based on ionized composite materials as functional materials not only need to have high device sensitivity, but also need to have no signal drift under constant pressure conditions and accurately feedback pressure information, so that the sensor can have the characteristics of both sensitivity and accuracy.
[0098] The prepared flexible pressure sensors were tested for pressure signal drift, that is, a fixed pressure value was applied to the sensor, and the long-term change of the capacitance signal was observed. The test results show that although the pressure sensor prepared based on the polyion elastomer control group has a relatively low sensitivity, the low creep and no leakage characteristics of the polyion elastomer material also enable it to perform long-term stable and accurate measurements under high pressure conditions, with basically no signal drift. On this basis, the performance of traditional polyion elastomers is optimized through the volume capacitance strategy. While ensuring the low creep and no leakage characteristics of the polyion elastomer material, the prepared sensor has a relatively high sensitivity while ensuring no signal drift through the addition of conductive fillers and the formation of volume capacitance. The specific signal drift test data is shown in the attached figure. Figure 11-14 shown.
[0099] So far, this patent has further proved the strategy of body capacitance advantage from technical principles to experimental data, and solved the contradiction between high sensitivity and low drift of current ionization pressure sensors from the intrinsic properties of materials. The obtained ionization composite material based on epoxy groups can be used as the sensor material layer to prepare an ionization pressure sensor with both high sensitivity and low drift, which is expected to be widely used in technical fields such as human-computer interaction and wearable medical devices.
[0100] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for preparing an ionizing composite material based on epoxy groups, characterized in that: The following steps are involved: Disperse material A, material B and material C uniformly in a solvent; evaporate the solvent from the obtained dispersion, and then solidify to obtain an ionized composite material based on epoxy groups; wherein material A is an ionic liquid with epoxy groups, including epoxy ionic liquid 1 and / or epoxy ionic liquid 2; material B includes an organic polyamine compound or a polyether amine; and material C is a conductive filler.
2. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 1, characterized in that: The material B includes tris(2-aminoethyl)amine and / or 2,2'-(ethylenedioxy)bis(ethylamine), and the material C includes carbon nanotubes and / or carboxyl-modified carbon nanotubes; The molar ratio of the material A to the material B is 2:(0.5-2), and the material C accounts for 2%-5% of the mass of the material A.
3. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 1, characterized in that: The epoxy ionic liquid 1 is prepared by the following method: S1: dissolving imidazole, sodium bicarbonate and 4-bromo-1-butene in acetonitrile, heating to reflux, and after the reaction is completed, filtering and rotary evaporation are performed to obtain a crude product; the crude product is purified by using dichloromethane and an extractant; a concentrated solution of LiTFSI is added dropwise to the purified product until no oily precipitate is produced, the upper aqueous phase is sucked out, impurities are extracted with deionized water, and residual water is removed; S2: dissolving the reaction product of step S1 and m-chloroperbenzoic acid in acetonitrile, reacting at room temperature for a period of time, filtering, and rotary evaporating to obtain a crude product; purifying the crude product with ether to obtain epoxy ionic liquid 1.
4. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 3, characterized in that: In step S1, the molar ratio of imidazole, sodium bicarbonate and 4-bromo-1-butene is 1:(0.8-1.2):(1.7-2.55).
5. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 3, characterized in that: In step S2, the molar ratio of the reaction product of step S1 to m-chloroperbenzoic acid is 1:(3.2-4.8).
6. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 1, characterized in that: The epoxy ionic liquid 2 is prepared by the following method: Dissolve imidazole, sodium carbonate, epichlorohydrin and LiTFSI concentrated solution in acetonitrile and heat under reflux. After the reaction is completed, filter and rotary evaporate to obtain a crude product. Purify the crude product with deionized water to obtain epoxy ionic liquid 2.
7. The method for preparing the ionizing composite material based on epoxy group as claimed in claim 6, characterized in that: The usage ratio of the imidazole, sodium carbonate, epichlorohydrin and LiTFSI concentrated solution is 1 mmol: (1.6-2.4) mmol: (1.6-2.4) mmol: (0.23-0.34) g.
8. An ionizing composite material based on epoxy groups prepared by the method according to any one of claims 1 to 7.
9. A high-sensitivity, low-drift ionization pressure sensor, characterized in that: It comprises a sensor material layer, an electrode layer and a packaging layer, wherein the sensor material layer comprises the epoxy group-based ionizing composite material according to claim 8, the packaging layer comprises a PDMS film, and the electrode layer comprises a PI / Cu composite film.
10. Application of the high-sensitivity, low-drift ionization pressure sensor according to claim 9 in the fields of human-computer interaction and wearable medical devices.
Citation Information
Patent Citations
Polyion elastomer as well as preparation method and application thereof
CN115785445A
Preparation method of PVDF-based composite film for pressure sensor
CN116607267A
Low-creep polyelectrolyte elastomer material, preparation method and drifting-free flexible pressure sensor prepared from low-creep polyelectrolyte elastomer material
CN118126249A
Integrated flexible pressure sensor based on ionic gel and preparation method thereof
CN118347612A
Ionic Liquid Epoxy Resin Monomers
US20110257409A1